Evaluating the Perceived Quality of Educational Services Among Clinical Pathology Residents in Hasanuddin University Using the SERVQUAL Instrument - Kartika Paramita; Andi Alfian Zainuddin; Berti Nelwan; Budu; Irfan Idris; Agussalim Bukhari (Education in Medicine Journal, 2026)
The SERVQUAL instrument is widely used to assess service quality across various sectors; however, its application in specialist medical education remains limited. This study evaluated the educational service quality of the Clinical Pathology Specialist Programme at Hasanuddin University, Indonesia, from the residents’ perspective using the SERVQUAL model. Out of 84 residents, 64 completed thestandardised questionnaire measuring five service dimensions: reliability, assurance, tangibles, responsiveness, and empathy. All dimensions showed negative quality gap scores, indicating that the perceived service fell short of expectations. The largest gap was found in responsiveness, reflecting delays or insufficient support in addressing the residents’ academic needs, whereas the smallest gap appeared in tangibles, suggesting relatively better satisfaction with facilities and staff appearance. The lowest- and highest-rated items were the availability of appropriate reading materials and the professional appearance of the staff, respectively. These findings highlight the need for targeted improvements, particularly in responsiveness and academic support. Persistent negative service gaps may undermine resident satisfaction, learning outcomes, and programme credibility. As postgraduate medical education shifts towards learner-centred, competency-based models, regular assessments using tools such as SERVQUAL are essential for guiding quality improvement, promoting institutional accountability, and supporting the development of competent clinical pathologists in Indonesia.